ANALISIS PEMECAHAN MASALAH PADA KURIKULUM MATEMATIKA SEKOLAH DI SINGAPORE DAN INDONESIA - Nur Fauziah Siregar; Iwan Junaedi; Mulyono Mulyono (Jurnal Karya Pendidikan Matematika, 2025)
Problem solving is one of the objectives of the mathematics curriculum in various countries. This study aims to describe the problem solving contained in the mathematics curriculum in Singapore and Indonesia. This research uses the Systematic Literature Review (SLR) method. The results obtained are the curriculum in Singapore is known as an education system that focuses on problem solving, supported by 5  interconnected components namely concepts, skills, processes, attitudes, and metacognition. With the education system in Singapore shows good results at the international level in the top three positions achieved by students. In the Indonesian curriculum, problem solving is one of the learning outcomes of mathematics. In learning mathematics, problem solving is used as a learning approach. The problem-solving approach can improve problem solving skills based on research results. Meanwhile, according to the results of PISA 2022 that Indonesian students have not achieved maximum results